Crecimiento vegetativo, producción y calidad de las fibras en plantas de algodonero sometidas a estrés mineral - Broetto, Fernando [UNESP] (2013)
Potassium, like nitrogen, it constitutes an essential element for growth, development and production of cotton crops. Moreover, these elements are directly related to fiber formation and when provided in suitable doses, influences its quality. The aim of the experiments was to evaluate the influence of potassium on biometric parameters, yield and quality of cotton fibers. For this purpose, plants of the cultivar Delta opal were grown in a greenhouse with altered potassium fertilization, simulating K deficiency and two overdoses. During the different phenological stages, biometric variables were analyzed including the production of fibers and their qualitative parameters. The sub-dose and the overdoses treatments of K, changed all the evaluated parameters, demonstrating the importance of potassium fertilizer on them.